Indigenous management practices in Africa : a guide for educators - Uzo, Uchenna; Kinoti Meru, Abel (Emerald Publishing Limited, 2018)
"Indigenous ManagementPractices in Africa: A Guide for Educators and Practitioners" is a timely response to the recent callfor management philosophies and theories that reflect the peculiarities of theAfrican continent. Western management models in Africa may not have yielded theresults required to trigger economic growth and development, yet Africa is fastbecoming the investment destination of firms operating outside the continent. This book unravels the indigenous management practices that shapethe way that organisations operate in Africa. It also addresses the differencesbetween indigenous African and western management practices, at the same time considering the implications for African business management. Insights from the book offera framework for developing African management curricula for business schools,both within and outside the continent. Practitioners aiming to expand theiroperations on the continent may also find valuable insights in this book onesthat may support and develop future management decisions.
Includes index.
Keywords: Industrial management -- Africa.; Indigenous peoples -- Africa.; Business & Economics -- Management.; Management & management techniques.; elektronické knihy; electronic books